Testing of chickens experimentally infected with A/H9N2 avian influenza virus isolates for their immune responses - O. S. Osipova; M. A. Volkova; S. V. Frolov; D. B. Andreychuk; I. A. Chvala (Ветеринария сегодня)
Data on tests of chickens for their immune responses to infection with low pathogenic А/Н9N2 avian influenza virus isolates belonging to Y-280 and G1 genetic lines are presented in the paper. CD4⁺/CD8⁺ ratios were determined with flow cytometry for initial immune status examination and for detection of apparent immune system disorders. Quantitative analysis of peripheral blood lymphocyte subpopulations in chickens revealed changes characteristic of the immune suppression. Analysis of dynamics of T- and B-lymphocyte levels in blood of the infected chickens revealed decrease in relative T-lymphocyte counts and increase in relative B-lymphocyte counts. T-lymphocyte subpopulation composition expressed as CD4⁺/CD8⁺ ratio (%) changed after the infection: CD4⁺ cell proportion was found to decrease whereas CD8⁺ cell proportion increased. According to literature data, immune response activated by vaccination induces the reverse dynamics towards to increase in CD4⁺/CD8⁺ ratio. Both cell-mediated immunity and humoral immunity play role in development of the immune response in chickens infected with avian influenza viruses. Apparent humoral immune response was detected by serological tests of sera taken from chickens on day 14 after infection. Mean specific anti-A/H9N2 AIV antibody titre in all groups of test chickens infected with low pathogenic avian influenza virus isolates was higher than 6 log₂ . High level of specific antibodies to avian influenza virus was indicative of postvaccinal humoral immune response development.